CSI, crime scene investigation. The complete tenth season [videorecording (DVD)] - Szmanda, Eric; Eads, George, 1967-; Fox, Jorja; Fishburne, Laurence, III, 1961-; Helgenberger, Marg; Guilfoyle, Paul; Langham, Wallace (CBS DVD, 2010)
The CSI team is on the case 24/7, scouring the scene, collecting irrefutable evidence, and finding the missing pieces that will solve the mystery.